Comparative Analysis of Refractive Result Predictability During Iridocapsular and Iridovitreal Fixation of Biplanar Intraocular Lens - B. E. Malyugin; E. N. Panteleev; A. N. Bessarabov; D. F. Pokrovskiy; A. S. Semakina; S. A. Abdullaeva (Oftalʹmologiâ)
Purpose: to carry out a comparative analysis of refractive outcomes and features during preoperational calculation of the biplanar intraocular lens (IOL) with iridocapsular and iridovitreal fixation.Patients and methods. Study included the analysis IOL model RSP-3 implantation after phacoemulsification cataract surgery with  subluxated lens grade 2. Analyzed 309 eyes of 304 patients with iridocapsular (n = 44) (ICF) and iridovitreal fixation (n = 265)  (IVF). In both groups IOL power was calculated with use of A- constant (118.2) recommended by manufacturer. Mean period of  examination was 6 months. To count optimized A-constant in both  groups we used next data: IOL power and axial length before  surgery, keratometry, spherical equivalent and IOL effective position  during 6 months after surgery.Results. In group with ICF postoperative refraction was achieved ± 0,5 D in 10 cases (23%), in group IVF — in 29 cases (11%). Mean  value of optimized A-constant for IOL model RSP-3 in groups with  ICF and IVF were 117.2 ± 1.18 (114.0–120.8) and 116.9 ± 1,89  (109.6 до 123.6). There were no statistically significant difference  between compared groups (p = 0.46).Conclusion. Use of A-constant recommended by manufacturer do  not allow achieving target refraction in most cases. Mean values of  biplanar IOL A-constant counted for ICF and IVF were 117,2 and  116,9 respectively, what should be taken into account during IOL  power count, according to its fixation method.